THE INFLUENCE OF EMPLOYER BRANDING AND CAREER DEVELOPMENT OPPORTUNITIES ON THE INTENTION TO APPLY AMONG EDUCATED YOUTH AT BUMDes DALUNG - Agus Riyan Adi Putra; I Gusti Lanang Suta Artatanaya; I Gede Sugita Aryandana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The low level of interest among educated youth in applying for positions at Village-Owned Enterprises (Badan Usaha Milik Desa/BUMDes) has become a challenge in strengthening human resources and ensuring the sustainability of rural economic development. This study aims to analyze the influence of employer branding and career development opportunities on the intention to apply among educated youth at BUMDes Dalung. The study employed a quantitative approach with a causal associative research design. The sample consisted of 150 respondents selected using a purposive sampling technique, comprising individuals aged 18–30 years with a minimum educational attainment of senior high school or its equivalent who were familiar with BUMDes Dalung. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that employer branding has a positive and significant effect on intention to apply (t = 5.138; p < 0.001). Similarly, career development opportunities also have a positive and significant effect on intention to apply (t = 2.795; p = 0.006). Simultaneously, both variables significantly influence intention to apply (F = 13.379; p < 0.001), with an Adjusted R Square value of 0.567, indicating that 56.7% of the variation in intention to apply can be explained by the research model. These findings underscore that strengthening the organization's image as a professional workplace, accompanied by the provision of clear and sustainable career development opportunities, constitutes an important strategy for BUMDes to enhance organizational attractiveness and attract high-quality young talent Keywords: Employer Branding; Career Development Opportunities; Intention to Apply